2014
DOI: 10.2298/gsf1410105m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the time of cuttings collection and IBA concentration on the rooting of softwood cuttings from elite trees of Cornelian cherry (Cornus mas L.) in Belgrade area

Abstract: In this study, the effect of concentration of indole-3-butyric acid (IBA) (powder dip), cutting type as well as the time of taking cuttings on the rooting of softwood cuttings of cornelian cherry was examined. Four types of cuttings were used: basal cuttings, terminal cuttings, basal cuttings with 2-year-old wood and terminal cuttings with 2-year-old wood. The obtained results showed that IBA concentration, cutting type and time of collecting have significant effect on rooting. The best resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 0 publications
3
9
0
1
Order By: Relevance
“…Length and diameter of cuttings exerts a significant effect on number of primary roots of cuttings ( Gautam et al (2010) reported that root induction was higher in cuttings with length ranging between 10 cm and 15 cm long than cuttings of length 5 cm in juvenile apical shoot cuttings of guava. Markovic et al (2014) obtained highest mean number of primary roots per cuttings (12.9) using terminal cuttings with current season's wood only, treated with 1% IBA (powder dip) in cornelian cherry. In the present study the different size of cuttings length and diameter has exhibited a significant effect on length and diameter of primary roots ( and diameter of primary roots (1.81 mm) was observed in cuttings of diameter 0.75 -1.00 cm.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Length and diameter of cuttings exerts a significant effect on number of primary roots of cuttings ( Gautam et al (2010) reported that root induction was higher in cuttings with length ranging between 10 cm and 15 cm long than cuttings of length 5 cm in juvenile apical shoot cuttings of guava. Markovic et al (2014) obtained highest mean number of primary roots per cuttings (12.9) using terminal cuttings with current season's wood only, treated with 1% IBA (powder dip) in cornelian cherry. In the present study the different size of cuttings length and diameter has exhibited a significant effect on length and diameter of primary roots ( and diameter of primary roots (1.81 mm) was observed in cuttings of diameter 0.75 -1.00 cm.…”
Section: Resultsmentioning
confidence: 99%
“…IBA can enhance tissue sensitivity to IAA and increase rooting (Vander Krieken et al, 1993). Markovic et al (2014) reported highest rooting percentage (96.7 %) in cornelian cherry by using terminal cuttings with current season's wood only, treated with 1% IBA (powder dip). Length and diameter of cuttings exerts a significant effect on number of primary roots of cuttings ( Gautam et al (2010) reported that root induction was higher in cuttings with length ranging between 10 cm and 15 cm long than cuttings of length 5 cm in juvenile apical shoot cuttings of guava.…”
Section: Resultsmentioning
confidence: 99%
“…The time of taking softwood cuttings is very important in the vegetative propagation of woody species and it influences rooting (G r b i ć , 2004;Marković et al, 2014;Hartmann et al, 2010). Our results show that the time of taking nodal cuttings for in vitro culture initiation can also influence bud proliferation and the success of culture establishment.…”
Section: Culture Establishment On Maymentioning
confidence: 99%
“…To date, wild-type populations of Cornelian cherry ( C. mas ) from several parts of the world have been successfully propagated via cuttings in the past with the use of external hormone application on hardwood and soft wood cuttings taken from mature individuals growing in the wild [ 37 , 38 ]. A popular hormonal substance that has been used in the past is indole-3-butyric acid (IBA) [ 39 , 40 ], frequently achieving high rooting rates.…”
Section: Introductionmentioning
confidence: 99%